Modeling of warranty cost for a lifetime warranty policy [electronic resource] - Pezhman Ahmadi Khoshbakht, 1986- (2013)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri) - Universiti Teknologi Malaysia, 2013